Cultural Utilisation of Mamandi Boe Asieng Panas in Postpartum Care of Bajo Buton Tribe - Minarti Minarti; Anita Anita; Wa Ode Nesya Jeni Samrida (Borneo Scientific Publishing, 2023)
The Bajo tribe in Bajo Bahari Village, Buton Regency, has long practiced the cultural tradition of Mamandi Boe Asieng Panas, a hot bath using salty water. This practice is believed by traditional birth attendants and the local community to expedite the healing process for mothers who have recently given birth. The purpose of this study was to determine the effect of the Mamandi Boe Asieng Panas tradition on the speed of uterine involution in postpartum mothers. The research method was quasi-experimental, involving an intervention where postpartum women underwent Mamandi Boe Asieng Panas after giving birth. The height of the fundus uteri (in cm) was measured on the third and seventh days postpartum. The results indicated a significant effect, with a p-value of 0.000 and a 95% confidence interval mean difference of 3.25 (21-56-22). In conclusion, postpartum women who received the Mamandi Boe Asieng Panas intervention experienced a faster decrease in uterine involution compared to those who did not participate in the tradition.